Exercise of rights of tuberculosis patients undergoing pharmacological treatment - Bianca Contreira de Jung; Lisbeth Natalit Ampudia Tafur; Luize Barbosa Antunes; Giovana Calcagno Gomes; Roxana Isabel Cardozo Gonzales
ABSTRACT Objectives: to know how people with tuberculosis undergoing treatment exercise their rights throughout daily life while experiencing illness. Methods: this qualitative study was developed from April to May 2015, with people with tuberculosis undergoing treatment in an outpatient clinic of the Municipal Tuberculosis Control Program in the city of Pelotas. Data were collected through semi-structured interviews and verified by content analysis, under the thematic modality. Results: people announced aspects that involved human rights pertaining to their experiences, and they had difficulties to achieve full rights to dignity, health, social security, and social services. Such rights were neither guaranteed by the State nor by their families. Final Considerations: it is necessary for health professionals and services to inform and equip people with tuberculosis, directly or indirectly, for the full exercise of their rights.